1985
DOI: 10.1021/ja00310a023
|View full text |Cite
|
Sign up to set email alerts
|

Rare examples of structurally characterized five-coordinate organocobalt complexes. Novel dynamic NMR evidence for synergistic enhancement of cis and trans effects in B12 models

Abstract: A major factor influencing Co-C bond stability both in B12 compounds and organocobalt BI2 models appears to be the coordination number. Five-coordinate complexes are unusually stable to Co-C bond thermolysis, but structurally characterized examples of five-coordinate organocobalt complexes are rare. None are known for cases where R is a bulky group, such as i-C3H7. We report two definitive examples of five-coordinate complexes of the type Co(saloph)R, where saloph = dianion of disalicylidene-o-phenylenediamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 0 publications
5
58
1
1
Order By: Relevance
“…Model studies have indicated that a weaker nitrogen donor ligand decreases the dissociation energy of the C-Co bond (33)(34)(35). Interest in this second hypothesis has been stimulated by extended x-ray absorption fine structure spectroscopy and x-ray crystallography studies on MMCoA mutase, which indicate displacement of the DMB lower axial ligand of 1 by a protein histidine in cob(II)alamin-bound MMCoA mutase, with a long Co-N bond (3,4,36).…”
Section: Discussionmentioning
confidence: 99%
“…Model studies have indicated that a weaker nitrogen donor ligand decreases the dissociation energy of the C-Co bond (33)(34)(35). Interest in this second hypothesis has been stimulated by extended x-ray absorption fine structure spectroscopy and x-ray crystallography studies on MMCoA mutase, which indicate displacement of the DMB lower axial ligand of 1 by a protein histidine in cob(II)alamin-bound MMCoA mutase, with a long Co-N bond (3,4,36).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are systems with electron-rich, often anionic ligands, and many are derived from macrocyclic ligand systems, [7][8][9][10][11] largely as a result of extensive modeling studies of vitamin B 12 . [12,13] Para-as well as diamagnetic square-pyramidal [14] and trigonal-bipyramidal [8] systems have been reported, and, in the course of the search for the elusive Co = O functional group, [15] a tetracoordinate amido-Co III complex was also structurally characterized. [11] All these complexes have interesting reactivities that are not observed in classical Co III systems, such as the efficient production of alkyl radicals [16] and CÀH activation.…”
mentioning
confidence: 99%
“…Recently the chemistry of vitamin B 12 and its model complexes have been attracted the biochemists, inorganic chemists and organometallic chemists [1]. During the past few decades the research works are primarily on the preparation of model complexes of vitamin B 12 and investigation of their chemical behavior [4][5][6][7][8][9][10][11][12][13][14][15]. The conclusions reached from model complexes are then compared with vitamin B 12 with a view to explore its reaction and functions.…”
Section: Introductionmentioning
confidence: 99%